Advanced Home Automation by using Raspberry Pi - et. al., Prof.Girish.R.Deshpande, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now-a-days everyone is involved using their gadgets most of the day for the cause of office works, social involvement or as a hobby. In such era control over the most common domes- tic equipment’s like lights, air conditioners coolers, washing machines, electronic entertainment equipment’s needs an automation sys- tem. The main feature of such an automation system is to control the domestic appliances from anywhere using mobile phone for the purpose. It should compatible with the mode, medium and convenience of the usage. Home automation now termed as the ‘Smart Home’ is a combination of most advanced technologies like Artificial Intelligence and Internet of Things. Having good control over common communicating equipment’s this is most helpful for better decisions over optimizing re- sources usage. This Paper focus on an implementation of such system containing android application that controls devices remotely for switching on and off. The same functionality extended for using voice control also by converting voice command to text to send on net- work.